"The Joy of Happenstance!" An Interview with the Poet, Kelwyn Sole. Issue 1 (2nd January 2019) - D'Arcy, Elizabeth
Abstract : In this interview, poet and critic Kelwyn Sole traces the trajectory of his development as a poet, whose collections date from the late 1980s up until today. He discusses the wide range of political ideas and aesthetic influences that have shaped his poetry to the demands of living in both apartheid and post-apartheid South Africa.